2022
DOI: 10.3390/molecules27185886
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Characterization, Anti-Oxidant, Anti-Enzymatic and Cytotoxic Effects of Artemisia verlotiorum Lamotte Extracts: A New Source of Bioactive Agents

Abstract: Artemisia verlotiorum Lamotte is recognized medicinally given its long-standing ethnopharmacological uses in different parts of the world. Nonetheless, the pharmacological properties of the leaves of the plant have been poorly studied by the scientific community. Hence, this study aimed to decipher the phytochemicals; quantify through HPLC-ESI-MS analysis the plant’s biosynthesis; and evaluate the antioxidant, anti-tyrosinase, amylase, glucosidase, cholinesterase, and cytotoxicity potential on normal (NIH 3T3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 89 publications
1
3
0
Order By: Relevance
“…At present, studies on crude polysaccharides from Artemisia ordosica are mainly focused on mice, pigs, and poultry, and studies on goats have not been reported. Weaned piglets' apparent digestibility of nutrients and feed conversion efficiency were markedly improved by a water extract of Artemisia ordosica (750 mg/kg) in a dose-dependent manner, as well as considerably reducing their DMI from 14 to 28 days [10]. According to our study, AOCP improved the digestibility of DM, CP, and ADF, and increased ADG and feed conversion ratios in cashmere goats.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…At present, studies on crude polysaccharides from Artemisia ordosica are mainly focused on mice, pigs, and poultry, and studies on goats have not been reported. Weaned piglets' apparent digestibility of nutrients and feed conversion efficiency were markedly improved by a water extract of Artemisia ordosica (750 mg/kg) in a dose-dependent manner, as well as considerably reducing their DMI from 14 to 28 days [10]. According to our study, AOCP improved the digestibility of DM, CP, and ADF, and increased ADG and feed conversion ratios in cashmere goats.…”
Section: Discussionsupporting
confidence: 50%
“…However, no application studies in sheep have been reported. Among the effective compounds of Artemisia ordosica crude polysaccharide, polysaccharides have better hydrophilicity and a variety of biological activities, such as enhancing cell-mediated antioxidant [10], anti-inflammation [11] and antitumor [12] activities. Broilers stimulated by LPS (100 g/kg) exhibit reduced immune function and production performance that is alleviated by AOCP [13].…”
Section: Introductionmentioning
confidence: 99%
“…or the use of reference compounds other than Trolox. A few recent studies report the antioxidant activity of methanolic extracts of various Artemisia species in comparison to Trolox 19 , 28 , 63 (Supplementary Table 2 ). Our results are in line with the trend observed by Trifan and colleagues for FRAP assay, in which A. absinthium displayed the lowest antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…The Artemisia genus and the member species are well-studied for their various biological activities [ 8 , 9 , 10 , 11 , 12 , 13 ]. Artemisia annua L. has demonstrated significant medicinal benefits because of the presence of artemisinin [ 14 ].…”
Section: Introductionmentioning
confidence: 99%